Effect of a rule change on concussions and other injuries in professional baseball. Issue 11 (25th May 2017) - Gary, Green; D'Angelo, John; Coyles, Jon; Valadka, Alex
Abstract : Objective: To evaluate the hypothesis that a rule change can lower the incidence of concussions and other injuries in professional baseball. Design: Retrospective review of professional baseball's electronic medical record system. All Minor (MiLB) and Major League Baseball (MLB) teams are required to use this system. Setting: Five full MiLB and MLB seasons in the United States and Canada. Participants: All players in MiLB and MLB were included. The 30 MLB clubs have 750 active players and play 162 games per season. MiLB has approximately 7500 active players on 200 teams that play 56-144 games annually. Intervention: Before the 2014 season, MLB instituted a rule limiting home plate collisions between base runners and catchers. Outcome measures: All concussions and other injuries at home plate from 2011 to 2015 were analysed by mechanism and player position. Main results: From 2011-2013, an annual average of 117 injuries occurred at home plate in both MiLB and MLB, with an average of 4823 days lost annually. An average of 13 concussions occurred annually in both MiLB and MLB. Following the rule change, in 2014-2015 there was an annual average of 60 home plate injuries with 1592 days lost. There were 6 MiLB home plate concussions in 2014 and none in 2015. There were no home plate concussions in MLB in 2014-2015 (p=0.07). MiLB and MLB combined for approximately 660, 000 athlete exposures per season. Conclusions: This rule change was associated with a strong trend toward reduced concussions and other injuries at home plate. Competing interests: Mr. D'Angelo and Mr. Coyles are employed by Major League Baseball. Dr. Green receives payment from Major League Baseball for his role as Medical Director. Dr. Valadka is a paid consultant to Major League Baseball. The authors have no other disclosures to report.